Cytotype polymorphism of the P-M system in two wild populations of Drosophila melanogaster. - Anxolabéhère, D (1982)
In Drosophila melanogaster the interactions of the P-M system generate germ-line aberrations (e.g., sterility, mutations) found in certain interstrain hybrids. Two wild populations, from France and Tunisia, were examined in order to determine the distribution of the chromosomal P factor and the extrachromosomal cytotypes. No P factors active for potential GD sterility were found in these populations. But search for the M cytotype, which causes susceptibility to the P factors, and for the P cytotype, which causes resistance to the P factors, showed that both populations are polymorphic for the cytotypes. Such a polymorphism seems to be stable in the wild, at least over a 2-year period. Mutator activity (measured by generated mutations at the sn and ras loci) was found to be present. Some possible interactions between cytotype polymorphism, mutator activity, and the structure of Drosophila populations are discussed.